The potential impact of melanosomal pH and metabolism on melanoma - You, Jaewon; Yusupova, Maftuna; Zippin, Jonathan H. (Frontiers in Oncology, 2022)
Melanin is synthesized in melanocytes and is transferred into keratinocytes to block the effects of ultraviolet (UV) radiation and is important for preventing skin cancers including melanoma. However, it is known that after melanomagenesis and melanoma invasion or metastases, melanin synthesis still occurs. Since melanoma cells are no longer involved in the sun tanning process, it is unclear why melanocytes would maintain melanin synthesis after melanomagenesis has occurred. Aside from blocking UV-induced DNA mutation, melanin may provide other metabolic functions that could benefit melanoma. In addition, studies have suggested that there may be a selective advantage to melanin synthesis in melanoma; however, mechanisms regulating melanin synthesis outside the epidermis or hair follicle is unknown. We will discuss how melanosomal pH controls melanin synthesis in melanocytes and how melanosomal pH control of melanin synthesis might function in melanoma. We will also discuss potential reasons why melanin synthesis might be beneficial for melanoma cellular metabolism and provide a rationale for why melanin synthesis is not limited to benign melanocytes.